Seeking an alliance between farmers and genebanks - Bordoni, P.; Gwinner, V. (2013)
In Bolivia and Malaysia, farmers are increasingly affected by drought, water logging and unpredictable weather patterns. To cope, they plant an array of traditional crops and varieties to spread the risk of crop loss, whether from pests, diseases or the weather. However for these farmers, agrobiodiversity is not just a way to insure against crop losses; it's an important source of cultural pride and value. Seventy three year old Don Victor, who farms at 4,100 metres above sea level in Colomi, Bolivia, maintains 39 varieties of native potato. ”These are like my family,” he says, sharing his planting material only with those he trusts.